Contribution of adiponectin polymorphisms to the risk of coronary artery disease in a North‐African Tunisian population - Ghazouani, Lakhdar; Elmufti, Afoua; Baaziz, Intissar; Chaabane, Ibtissem; Ben Mansour, Hedi (Journal of clinical laboratory analysis, 2018)
Background Adiponectin, an adipocyte‐derived protein, is known to play a key role in the processes leading to atherosclerosis and coronary artery disease (CAD) through its anti‐atherogenic, anti‐inflammatory, antioxidative, and anti‐apoptotic properties. In the current study, we have studied the association of two single nucleotide polymorphisms (SNPs) +45 T>G (rs2241766) and +276 G>T (rs1501299) of the adiponectin gene with coronary artery disease (CAD) on an Arab/North‐African population from Tunisia. Methods Subjects comprised 277 patients with angiographically demonstrated CAD and 269 age‐ and gender‐matched control subjects. The adiponectin genotypes were performed by polymerase chain reaction‐restriction fragment length polymorphism analysis (PCR‐RFLP). The contribution of adiponectin variants to CAD was analyzed by haplotype and regression analysis. Results Adiponectin +45T>G and +276G>T genotypic and allelic distributions did not show a significant difference between cases and controls. Similarly, no association with CAD was observed for the haplotype analysis. Assuming dominant model of transmission for both polymorphisms and after adjustment of a number of traditional risk factors for CAD, logistic regression analysis showed an association of SNP +45 T>G with increased risk of developing CAD [adjusted OR (95% CI) = 2.59 (1.17‐5.70); P = .01]. However, SNP + 276 G>T is associated with decreased risk of developing CAD [adjusted OR (95% CI) = 0.47 (0.22‐0.97); P = .04]. Conclusion There is no allelic or genotypic association of +45 T>G and +276 G>T of the adiponectin gene with CAD in the Tunisian population.